Various defects in graphene: a review - Bhatt, Mahesh Datt; Kim, Heeju; Kim, Gunn (RSC advances, 2022)
Pristine graphene has been considered one of the most promising materials because of its excellent physical and chemical properties. However, various defects in graphene produced during synthesis or fabrication hinder its performance for applications such as electronic devices, transparent electrodes, and spintronic devices. Due to its intrinsic bandgap and nonmagnetic nature, it cannot be used in nanoelectronics or spintronics. Intrinsic and extrinsic defects are ultimately introduced to tailor electronic and magnetic properties and take advantage of their hidden potential. This article emphasizes the current advancement of intrinsic and extrinsic defects in graphene for potential applications. We also discuss the limitations and outlook for such defects in graphene. Intrinsic and extrinsic defects in graphene affect the performance of graphene in applications such as electronic devices, transparent electrodes, and spintronic devices.